PENGARUH KOMPETENSI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA - Basri, Basri; Hamris, Saddiya (Jurnal Metaverse ADPERTISI, 2024)
The purpose of this study is to find out and analyze the Influence of Competence and Leadership Style on Employee Performance through Work Motivation at PT. Pawnshops in the Bantaeng Area directly or indirectly. The analysis method used is Path Analysis using SmartPLS Software, the purpose is to describe the actual state of the research object to find out the Competence and Leadership Style on employee performance through motivation at the Bantaeng Area Pawnshop Office through the submission of statements in questionnaires to employees. The results of the research obtained are (1) Competence has a Positive and Significant Effect on Work Motivation in PT. Pawnshop Bantaeng Area, (2)  Leadership Style has a Positive and Significant Effect on Work Motivation at PT. Pegadaian Bantaeng Area (3) Motivation has a Positive and Significant Effect on Performance at PT. Pawnshop Bantaeng Area.( 4) Competence has a Positive and Significant Effect on Performance at PT. Pegadaian Bantaeng Area, (5) Leadership Style has a Positive and Significant Effect on Performance at PT. Pegadaian Bantaeng Area, (6) Competence has a Positive and Significant Effect on Performance through Employee Work Motivation at PT. Bantaeng Area Pawnshop, and (7) Leadership Style has a Positive and significant effect on performance through Work Motivation at PT. Pawnshop in Bantaeng Area.